Pengaruh Perendaman Terhadap Mutu Tepung Sagu (Metroxylon sp.) di Kampung Tambat Kabupaten Merauke - Witdarko, Yus; Jamaludin, Jamaludin; Parjono, Parjono; Pamungkas, Wiyan Afriyanto (AGRICOLA, 2022)
This study aims to identify the quality of "Dwitrap" 1 kg sago flour by providing soaking treatment with various types of water: water from Kampung Tambat; well water; mineral water; and gallon water for 12 hours and 24 hours of soaking time to achieve the quality of sago flour according to SNI 01-3729-2008. The results obtained indicate that the treated sago flour has a quality following SNI 01-3729-2008 in terms of the water content parameter (KA), about 13%. The pH values ​​ranging from 6-7 also indicate that the sago flour produced does not contain excess organic acids, which can cause sago to have an acidic taste. The content of crude fibre and fineness of flour that passes a 100 mesh sieve obtained is not yet with the SNI quality standard, so it is necessary to make improvements in the sago processing process, for example, with a sieving machine so that the fibres from the sago stalks are not included and reduce the quality of sago flour. The results obtained indicate that soaking treatment improves the quality of "Dwitrap" sago flour.